Literatur Review Pelaksanaan Ronde Keperawatan di Ruang Rawat Inap Rumah Sakit - Posma Sinta Rotua; Bertha Tri Sumartini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background, Nursing rounds are a form of nursing round method in providing nursing care in a team MAKP (Professional Nursing Care Model). This systematic round is statistically believed to be able to reduce the use of bells to call nurses, the possibility of patient falls, anxiety and increase patient satisfaction.Purpose, This literature review aims to identify and analyze the implementation and influence of Nursing Rounds in Hospitals.Methods,There were 14 journals used in the literature review. Journal searches are carried out through Four databases : Google Scholar, Crossref, ProQuest, Emerald Insight.Results, Analysis of the literature review shows that Nursing Rounds can be applied to inpatient rooms provided that team MAKP is used, there is cooperation between nurses, reducing workload because it can be adjusted to the implementation of nursing care.Conclusion, Nursing rounds are implemented in the inpatient room by fulfilling requirements such as using team MAKP, collaboration between nurses and implementation of nursing care.